Penggunaan Metode Bercerita dan Penafsiran Perumpamaan Anak yang Hilang dari Sudut Pandang Non-Soteriologis. - Roesmijati Roesmijati (STT Kingdom, 2023)
Many teaching methods are used by teachers to teach the truth of God’s word. One of the teaching methods used by Jesus is the storytelling method. The storytelling method is synonymous with teaching young children, but actually, the storytelling method can also be used in teaching adults. In Luke 15:11-32 Jesus told the parable of the prodigal son. The purpose of writing this research is to understand the storytelling method and explain the interpretation of the parable of the prodigal son. There are still many interpreters who only emphasize one side, namely soteriologically, and are poorly interpreted from outside the soteriological framework. This research discusses storytelling methods and theological studies of the parable of the missing children using the library research method.